Inhibition of PDGFR by CP-673451 induces apoptosis and increases cisplatin cytotoxicity in NSCLC cells via inhibiting the Nrf2-mediated defense mechanism. (1st October 2018) - Yang, Yang; Deng, Yanchao; Chen, Xiangcui; Zhang, Jiahao; Chen, Yueming; Li, Huachao; Wu, Qipeng; Yang, Zhicheng; Zhang, Luyong; Liu, Bing
Graphical abstract: Highlights: Inhibition of PDGFRβ induces apoptosis in NSCLC cells via inhibiting Nrf2. CP-673451 suppresses transcriptional Nrf2 expression via inhibiting PI3K/Akt. Inhibition of PDGFRβ sensitizes NSCLC cells to cisplatin. Abstract: Platelet-derived growth factor receptors (PDGFRs) are abundantly expressed by stromal cells in the non-small cell lung cancer (NSCLC) microenvironment, and in a subset of cancer cells, usually with their overexpression and/or activating mutation. However, the effect of PDGFR inhibition on lung cancer cells themselves has been largely neglected. In this study, we investigated the anticancer activity of CP-673451, a potent and selective inhibitor of PDGFRβ, on NSCLC cell lines (A549 and H358) and the potential mechanism. The results showed that inhibition of PDGFRβ by CP-673451 induced a significant increase in cell apoptosis, accompanied by ROS accumulation. However, CP-673451 exerted less cytotoxicity in normal lung epithelial cell line BEAS-2B cells determined by MTT and apoptosis assay. Elimination of ROS by NAC reversed the CP-673451-induced apoptosis in NSCLC cells. Furthermore, CP-673451 down-regulated the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) probably through inhibition of PI3K/Akt pathway. Rescue of Nrf2 activity counteracted the effects of CP-673451 on cell apoptosis and ROS accumulation. Silencing PDGFRβ expression by PDGFRβ siRNA exerted similar effects with CP-673451 in A549 cells, and when PDGFRβ was knockdowned by PDGFRβ siRNA, CP-673451 produced no additional effects on cell viability, ROS and GSH production, Nrf2 expression as well as PI3K/Akt pathway activity. Specifically, Nrf2 plays an indispensable role in NSCLC cell sensitivity to platinum-based treatments and we found that combination of CP-673451 and cisplatin produced a synergistic anticancer effect and substantial ROS production in vitro . Therefore, these results clearly demonstrate the effectiveness of inhibition of PDGFRβ against NSCLC cells and strongly suggest that CP-673451 may be a promising adjuvant chemotherapeutic drug.